The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1080/15287390500194441
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Acute Exposure Guideline Levels (AEGLs) for Chemical Warfare Nerve and Sulfur Mustard Agents

Abstract: Acute exposure guideline levels (AEGLs) have been developed for the chemical warfare agents GB, GA, GD, GF, VX, and sulfur mustard. These AEGLs were approved by the National Advisory Committee for Acute Exposure Guideline Levels for Hazardous Substances after Federal Register publication and comment, and judged as scientifically valid by the National Research Council Committee on Toxicology Subcommittee on AEGLs. AEGLs represent general public exposure limits for durations ranging from 10 min to 8 h, and for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 155 publications
0
54
0
Order By: Relevance
“…scrotum, anal region) are highly sensitive to SM vapor (Kehe and Szinicz, 2005). The onset of symptoms depends on the absorbed agent dose and follows Haber's rule, where higher doses are known to shorten the symptom free latency period (Miller et al, 2000;Watson et al, 2006). However, in case of SM, the effect that increasing exposure shortens the latency period is not only governed by Haber's rule, but also influenced by the specific mechanism of SM toxicity: lower-dose exposures to SM predominantly result in DNA damage and effects become evident only after a latency period, when cells undergo cell cycle arrest and possibly apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…scrotum, anal region) are highly sensitive to SM vapor (Kehe and Szinicz, 2005). The onset of symptoms depends on the absorbed agent dose and follows Haber's rule, where higher doses are known to shorten the symptom free latency period (Miller et al, 2000;Watson et al, 2006). However, in case of SM, the effect that increasing exposure shortens the latency period is not only governed by Haber's rule, but also influenced by the specific mechanism of SM toxicity: lower-dose exposures to SM predominantly result in DNA damage and effects become evident only after a latency period, when cells undergo cell cycle arrest and possibly apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Such is the case for the CWAs and TICs evaluated in the present assessment (NRC/COT 2002, 2003; Watson et al 2006a,b). …”
Section: Precedents and Sources Of Exposure Guidelinesmentioning
confidence: 65%
“…Army Corps of Engineers Baltimore District 2007; PARSONS 2007; DDESB 2008). These authorities consider the toxicity endpoints and uncertainty factors applied during development of arsine and sulfur mustard AEGL-2 concentrations to be protective (NRC/COT 2000, 2003; Watson et al 2006a). …”
Section: Precedents and Sources Of Exposure Guidelinesmentioning
confidence: 99%
“…There is relatively little quantitative data on human inhalation exposures. Some early human exposures performed in 1918 and others performed in 1941–1942 and summarized by Watson (2006) suggest that exposure to SM at concentration × time doses of 1–100 mg × min/m 3 caused increasingly severe ocular effects and skin burns, with some evidence of mucosal exfoliation in the nasopharynx. Early exposures of rabbits summarized in the same review indicated that respiratory lesions occurred at exposures of approximately 600 mg × min/m 3 .…”
Section: Discussionmentioning
confidence: 99%